KOMBINASI ORNAMEN BALI UTARA DAN BALI SELATAN PADA PINTU KUWADI - I Kadek Komara Yana; I Made Jana; I Made Sumantra (Pusat Penerbitan LP2MPP ISI Denpasar, 2022)
Internship/work practice is a form of lectures through work activities directly in the world of work. This internship program aims to improve and hone skills and deepen understanding as well as work motivation in the development of soft skills and hard skills. The method used in the implementation of the apprenticeship method is data collection through observation, interviews, and documentation carried out at Galih Ukir related to the creation that is carried out. The implementation of the internship is carried out by the creation process using the method of crafting according to Gustami, which is divided into 3 stages in the creation process, the exploration stage includes data collection and extracting ideas. Second, the design stage includes pouring out ideas in visual form in the form of basic sketches, alternatives and working drawings. Third, the embodiment stage, namely making it happen through the processing of raw materials, assembling, engraving and finishing. The result of the internship at Galih Ukir was getting an understanding and training on the creation of kuwadi door products with modern concepts without losing the traditional character. So that a kuwadi door is created with a modern concept that is decorated with a combination of North and South Bali ornaments with a white wash finishing technique so as to create an antique impression on the product.